2019
DOI: 10.1029/2018ja025318
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence‐Based Quantification of Dynamical Complexity in the Earth's Magnetosphere at Geospace Storm Timescales

Abstract: Magnetic storms are the most prominent global manifestations of out‐of‐equilibrium magnetospheric dynamics. Investigating the dynamical complexity exhibited by geomagnetic observables can provide valuable insights into relevant physical processes as well as temporal scales associated with this phenomenon. In this work, we utilize several innovative data analysis techniques enabling a quantitative nonlinear analysis of the nonstationary behavior of the disturbance storm time (Dst) index together with some of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 118 publications
(250 reference statements)
4
30
0
2
Order By: Relevance
“…SampEn is more stable than the frequently used approximate entropy ApEn with respect to variations of maximum allowed distance r and series length N (Richman & Moorman, ). But it still requires a selection of the most appropriate parameters N, r, m, and τ for a given application (Donner et al, ; Yentes et al, ).…”
Section: Correlations Between Sample Entropy Of Geomagnetic Indices Amentioning
confidence: 99%
See 4 more Smart Citations
“…SampEn is more stable than the frequently used approximate entropy ApEn with respect to variations of maximum allowed distance r and series length N (Richman & Moorman, ). But it still requires a selection of the most appropriate parameters N, r, m, and τ for a given application (Donner et al, ; Yentes et al, ).…”
Section: Correlations Between Sample Entropy Of Geomagnetic Indices Amentioning
confidence: 99%
“…The selection of such parameters was performed here (see full details in Appendix ) based on recommendations from previous works using SampEn (Balasis et al, ; Cao, ; Donner et al, , ; Yentes et al, ). These works have demonstrated that SampEn could really discriminate between storm and non‐storm periods as accurately as other refined metrics, such as recurrence quantification analysis (Donner et al, , ) when appropriate parameters are used. These parameters must represent a reasonable compromise between different constraints.…”
Section: Correlations Between Sample Entropy Of Geomagnetic Indices Amentioning
confidence: 99%
See 3 more Smart Citations